Mercedes Dantas e os discursos sobre a viagem pedagógica aos estados do Norte/Brasil (1930) - Amaral, Rosemeire dos Santos (2019)
The present Thesis is inserted in the research line of History, Society and Educational Thought, along with the Graduate Program in Education (PPGED) of the Federal University of Sergipe (UFS) and it is based on the discussions about the pedagogical trips taken by intellectuals and professionals in education, both internationally (Europe and the United States) and nationally, within a circuit of the Intellectual History of Education. The focus is the Professor Mercedes Dantas de Itapicurú Coelho (1900-1982) and the speeches on the pedagogical trip to the Northern States of Brazil in 1930. The general objective was to understand who was Professor Mercedes Dantas and the speeches produced by the press about her pedagogical trip to the Northern States, Brazil, in 1930. As specific objectives: to elaborate a biobibliographical profile of Mercedes Dantas, highlighting the institutional and social positions she has occupied; to list the speeches produced by the press about the trip taken in each state and, finally, to problematize the referred discursive statements of the trip and the Fernando de Azevedo Reform and its possible diffusion in the visited states. The data obtained from excerpts‟ information of the printed newspapers from the 1920 and 1930s - A manhã (RJ), A Noite (RJ), A Província (PE), Correio da Manhã (RJ), Diário da Manhã (ES), Jornal do Brasil (RJ), Jornal do Comércio (RJ - AM), O Globo (RJ), O Paiz (RJ), Pequeno Jornal, Jornal Pequeno (PE), among others - accessed through the National Digital Library (BNDigital), from digital signatures and from a particular historical source, a collection of newspaper and magazine clippings prepared and organized chronologically (1911-1947), Mercedes Dantas's “Notebook of Remembrance” - were investigated through the theorizations that constitute the Discourse Analysis (AD), following the French line, based on the postulates of the philosopher and historian Michel Foucault (1926-1985). The Mercedes teacher, a woman, single, young, patrícia, teacher, writer, journalist, politician and scholarly intellectual, who, in the 1930s, managed to transgress social and cultural standards, entering spaces and sectors, often exclusive to "men of letters", illustrious and ruling characters. She became a traveler and, in the role of ambassador, propagated the aspirations of the New School, participated in the clash between the Brazilian Association of Education and the National Federation of Education Societies, an important dissidence, propagated the principles of the Educational Reform of Fernando de Azevedo throughout the states of Northern Brazil, and ensured the grouping of the educational societies of the states. This woman, undoubtedly, deserves to be included in the Brazilian Historiography and in the Intellectual History of Education. The pedagogical trip to Northern Brazil states, based on the speeches extracted from the printouts, in turn, was configured as a case/event of national recognition and of great importance for the educational renewal of the country. Based on the Fernando de Azevedo Public Instruction Reform, in particular, of the primary education and the establishment/affiliation of teachers‟ societies from the respective places, as presented in the “Notebook of Remembrance”, where were highlighted the production and emergency conditions and the process of internalization and acceptability or not, as well as the moment of rupture of the speeches related to institutional practices and power relations. The Thesis pointed out that the research on the intellectual production, personal and professional life of Professor Mercedes Dantas - for the lack of researches that look into her character or for representing a prominent personality in the Brazilian educational field, although she remained “behind of the curtains” or at least “forgotten” by Brazilian historiography - is a valuable contribution to the knowledge production in the field of History of Education and the formation / performance of teachers and intellectuals in the 1920s and 1930s.